Rendimiento escolar en comunicación en niños de 5 años de programas escolarizados y no escolarizados (Red 9 - Callao) - Cruz Luyo, María Lucrecia (2010)
The following research is a descriptive and comparative study aimed to compare the school performance in the communicative area between 5 years-old students that belong to preschools with and without school educational formats (IIEEIIPRONOEIS), from Red No. 09, Callao. In this study, 135 students were taken into account: 105 students belonged to preschools with school educational formats (IIEEII), and 30 students belonged to preschools without school educational formats (PRONOEIS). All of them were 5 years old, female and male, from a low to middle socio economic status. The results showed that regarding the oral expression and comprehension skills area and the text comprehension and production skills area, there were not significant differences in their school performance among them.